2004
DOI: 10.1007/s00405-004-0803-3
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic muscles and distribution of the recurrent laryngeal nerve in the pig larynx

Abstract: To use the pig larynx in studies of laryngeal reinnervation, it is essential to have a clear understanding of its anatomy. We aimed to define the macroscopic anatomy of the intrinsic muscles and the course of the recurrent laryngeal nerve (RLN) in the pig larynx. Twelve large white pig larynges were used. Five larynges were preserved in formalin, then dissected to study the anatomy of the intrinsic muscles. Seven larynges were stained using the modified Sihler's staining technique, which results in nerves bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…Structurally, pig larynges also have a false and true vocal fold separated by a ventricle 15 but differ with a single muscular compartment posterior cricoarytenoid muscle. 17 Furthermore, the lamina propria in a pig vocal fold is made of two layers, 15,16 and creation of a microflap is hindered by submucosal glands in the glottis. 16 While pig vocal folds are similar to human vocal folds, Garrett et al found the dog vocal fold to be most similar to a human vocal fold based on histologic analysis and location of a microflap plane of elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, pig larynges also have a false and true vocal fold separated by a ventricle 15 but differ with a single muscular compartment posterior cricoarytenoid muscle. 17 Furthermore, the lamina propria in a pig vocal fold is made of two layers, 15,16 and creation of a microflap is hindered by submucosal glands in the glottis. 16 While pig vocal folds are similar to human vocal folds, Garrett et al found the dog vocal fold to be most similar to a human vocal fold based on histologic analysis and location of a microflap plane of elevation.…”
Section: Discussionmentioning
confidence: 99%
“…One successful laryngeal transplant has been performed on a human subject [13], and the patient continues to do well in terms of speech and swallowing 7 years later ( [14]; Strome 2005, personal communication). Limited re-innervation did occur in this patient, and the problem of functional restoration is under study in several human and animal models, including the pig [15][16][17]. However, several questions regarding long-term survival and immunosuppression need to be answered before routine clinical use can be advocated.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our experience with pig models, the dimensions of the larynx in a 30 to 40 kg pig are similar to that of the adult human (Garrett, Coleman et al 2000;Jiang, Raviv et al 2001). The vocal folds have a similar configuration, and the intrinsic muscles and distribution of the recurrent laryngeal nerve is similar as demonstrated by detailed dissections of cadaveric porcine laryngeal neuromuscular anatomy (Knight, McDonald et al 2005). Other phonatory characteristics such as rotational mobility of the cricothryoid joint, and relative size and innervation of the cricothyroid muscle have also been studied and found to be similar to that of humans (Jiang, Raviv et al 2001); although these features are not of direct relevance to endoscopic laryngeal microsurgery.…”
Section: Porcine Modelsmentioning
confidence: 82%
“…The presence of a superior and inferior fold could relate to the thyroarytenoid muscle having two separate bellies (Knight, McDonald et al 2005). It has been suggested that the inferior fold is the true vocal fold and the superior fold is akin to the ventricular fold in humans.…”
Section: Porcine Modelsmentioning
confidence: 99%